Civil competences of the head of a social institution as an important prerequisite for national security of the country - Hren, L. M.; Chebotarev, Mykola (My University, 2021)
Social work is aimed at meeting the vital and social needs of man. An important mission is assigned by the state to the head of a social institution who has a high level of professional competence. Competence is a key concept that characterizes the quality of professional training of the head of a social institution, his readiness for social activities and is one of the important factors in improving the quality of social services in the state. The essential features of the state personnel policy confirm the need for high professional competence in public administration. Competence is a concept that logically comes from attitudes to values and from skills to knowledge. The head of a social institution must have formed civic competencies, which is a prerequisite for national security. Participation in international projects (for example, in the Swiss-Ukrainian project "Development of Civic Competences in Ukraine – DOCCU") aims to use the best international experience in the formation of civic competences, promotes awareness of educators, civil servants, local governments on democratic citizenship and human rights. The structure of civic competence of the head of a social institution, which contains cognitive, value and activity components. Such projects contribute to the creation of conditions for the head of a social institution to acquire skills of civil law activity, self-organization and self-government. Conclusions and prospects for further research. So, based on the above, we came to the following conclusions: - the level of formation of civic competencies of the head of the social institution is an indicator of his readiness to perform his professional duties; - civic competencies of the head of a social institution, based on the national interests of the state, are an important prerequisite for national security; - We see the introduction of the obligatory discipline "Formation of civic competencies of the future head of a social institution" in the educational program "Social work" as a promising direction of further research.
Keywords: head of a social institution; social work; civic competencies; country; national security